KUALITAS PELAYANAN KESEHATAN GRATIS DI RUMAH SAKIT UMUM KABUPATEN NABIRE PAPUA. - KAMIROKI, ELLYS; RORONG, ARIE; RURU, JOORIE (Sam Ratulangi University, 2018)
Abstract: The purpose of this study was to find out the quality of free public health service in Nabire district general hospital.Research benefits as an information material for district goverments and communities. The method used is qualitativemethod with descriptive appoarch type and research location at general hospital of Nabire district. Based on the results ofresearch in accordance with the speed,timelines of service,accurate and quality but in the district general hospital Nabireuntil now the quality of healt services is not timely in health services and provide inaccurate data in the service and qualitythat is given has not run well in public health service because the quality of free public health service in Nabire districtpublic hospital has not done well. So in the free public health service in public hospitals Nabire should be improved so thatpublic health services in the Nabire district public hospital can be effective.Keywords: Quality, Health Sevices, Free